2021
DOI: 10.7717/peerj.12119
|View full text |Cite
|
Sign up to set email alerts
|

Level of anxiety among healthcare providers during COVID-19 pandemic in Saudi Arabia: cross-sectional study

Abstract: Background The burden of the spread of the COVID-19 pandemic has impacted widely on the healthcare providers physically and mentally. Many healthcare providers are exposed to psychological stressors due to their high risk of contracting the virus. Aims This study aimed to measure the level of anxiety among healthcare providers during the COVID-19 pandemic in Saudi Arabia. In addition, this study aimed to measure the level of anxiety based on demographic characteristics. Method A cross-sectional survey was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…AlAteeq et al found that more than half of healthcare providers had generalized anxiety and depression (51.4% and 55.2% respectively) [ 20 ]. Al Mutair et al found that 43.5% of healthcare providers in Saudi Arabia suffer from anxiety [ 21 ]. On the other hand, it was demonstrated that non-Saudi healthcare providers in Saudi Arabia experienced high levels of depression and anxiety compared to their Saudi peers [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…AlAteeq et al found that more than half of healthcare providers had generalized anxiety and depression (51.4% and 55.2% respectively) [ 20 ]. Al Mutair et al found that 43.5% of healthcare providers in Saudi Arabia suffer from anxiety [ 21 ]. On the other hand, it was demonstrated that non-Saudi healthcare providers in Saudi Arabia experienced high levels of depression and anxiety compared to their Saudi peers [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to the rapid increase in the number of COVID-19 cases, the government has taken drastic measures to control the spread of the virus, including a lockdown and travel restrictions that were introduced in March, 2020 ( Ministry of Health, 2020b ). The ongoing COVID-19 pandemic, along with the measures to control it, including quarantine requirements, can induce mental health issues, such as anxiety and depression ( Al Mutair et al., 2021b ; Al Mutair et al., 2021a ). This is especially a concern because the rapid increase in the number of COVID-19 cases has caused healthcare centers and hospitals in Saudi Arabia to extend the number of hours healthcare providers work, placing a significant amount of stress.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study in HCWs in Egypt [18] has shown that 90.5% of them presented different degrees of anxiety (32% and 18.5% presented moderate and severe anxiety symptoms, respectively). Also, the study [19] in Saudi Arabia showed a level of moderate anxiety of 28.9% and severe anxiety of 27.5% in HCWs coinciding with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety often leads to depression resulting in a mixed anxious-depressive disorder. Several studies evaluated and associated both neuropsychiatric disorders in HCWs [6,7,13,14,16,18,21,22]. The HCWs from VP-19 who presented higher anxiety levels have also reported moderate levels of depression during the first outbreak of COVID-19 in Peru [5].…”
Section: Discussionmentioning
confidence: 99%